Anglo-Panjabi technical terms : school subjects = Aṅgrezī-Pañjābī saṅketāwalī : sakūla-mazamūna (Laṛī (Patiala and East Punjab States Union (India). Mahikamā Pañjābī)) ;, 1953)
Dictionary of technical terms.